Gallium-68 perfusion positron emission tomography/computed tomography to assess pulmonary function in lung cancer patients undergoing surgery. Issue 1 (December 2016) - Le Roux, Pierre-Yves; Leong, Tracy; Barnett, Stephen; Hicks, Rodney; Callahan, Jason; Eu, Peter; Manser, Renee; Hofman, Michael
Abstract Background Pre-operative evaluation of lung cancer patients relies on calculation of predicted post-operative (PPO) lung function based on split lung function testing. Pulmonary perfusion (Q) PET/CT can now be performed by substituting Technetium-99 m labeling of macroaggregated albumin (MAA) with Gallium-68. This study compares Q PET/CT with current recommended methods of pre-operative lung function assessment. Methods Twenty-two patients planned for curative surgical resection (mean FEV1 77 %, SD 21 %; mean DLCO 66 %, SD 17 % predicted) underwent pre-operative Q PET/CT. Sixteen patients also underwent conventional lung scintigraphy. Lobar and lung split PPO lung function were calculated using Q PET/CT and current recommended methods, i.e. calculation based on anatomical segments for lobar function, and conventional perfusion scan for pneumonectomy. Bland-Altman statistics were used to calculate agreement between methods for PPO FEV1 and PPO DLCO. Results While mean split lobar functions were comparable, there was variation on an individual level between Q PET/CT and the anatomical method, with absolute difference over 5 % and 10 % in 37 % and 11 % of patients, respectively. For lobectomy the mean difference in PPO FEV1 was−1.2, but limits of agreement were−10 to 8.1 %. For DLCO, values were−1.1 % and−9.7 to 7.5 %, respectively. For pneumonectomy, PPO FEV1 values were−0.4 and−5.9 to 5.1 %. For DLCO, values were 0.3 % and−5.1 to 4.6 %. Conclusions While anatomic estimation provides "fixed" results, split lobar functions computed with Q PET/CT vary widely, reflecting the intra and inter-individual variability of regional lung function. Further studies to assess the role of Q PET/CT in predicting peri-operative risk in lung cancer patients planned for lobectomy are warranted.